The Effect of Foot Massage on Decreasing Peripheral Neuropathy Diabetic Complaints in the Patients with Type 2 Diabetes Mellitus - Ni Luh Putu Inca Buntari Agustini; Nadya Tressna Wulansari; Yustina Ni Putu Yusniawati; Ni Wayan Sintia (Universitas Airlangga, 2019)
Background: Peripheral neuropathy diabetic is a problem that will be experienced by almost all patients with type 2 diabetes mellitus (T2DM). One of the non-pharmacological therapies that can be done to reduce the complaints of peripheral neuropathy diabetic is foot massage. The purpose of this study was to determine the effect of foot massage on decreasing peripheral neoropathy diabetic complaints.Method: The research design was a one group pretest-post-test design (foot massage) as the treatment given to the patients with T2DM. The population in this study was the patients with T2DM who had peripheral neuropathy diabetic. Seventy-two participants were involved as the sample of the study selected through simple random sampling. The data was collected using the questionnaire of the Michigan Neuropathy Screening Instrument.Result: The results were analyzed using the Wilcoxon Sign Rank test with a significance level was set at α = 0.05.Conclusion: The foot massage had a significant effect at reducing the complaints of peripheral neuropathy diabetic in patients with T2DM (p=0,000 < ɑ 0.05). The patients with T2DM are expected to practice foot massage independently.